Risk of Retinal Vascular Occlusive Disease in Patients with Aortic Stenosis - Minjeong Kim, MD; Eui-Young Choi, MD, PhD; Kunho Bae, MD; Ju-Yeun Lee, MD, PhD (Ophthalmology Science)
Objective: The intersection of aortic stenosis (AS) and retinal vascular occlusive disease (RVOD) underscores the need for comprehensive cardiovascular and ophthalmic evaluations in patients with either condition. We aimed to evaluate the risk of RVOD in the entire Korean population with AS. Design: A population-based retrospective cohort study. Participants: We included 4094 patients with AS (2088 males) and 4094 age-, sex-, and index year-matched controls. Clinical and follow-up data of all patients diagnosed with AS and healthy controls from 2004 to 2015 were extracted from the Korean National Health Insurance Claim database. Methods: The risk of RVOD, including retinal vein occlusion and retinal artery occlusion, was compared between the AS and control groups. Competing analysis was used to obtain aHRs. The covariates used in the final analysis included age, sex, income, body mass index, fasting glucose, systolic blood pressure, cholesterol level, smoking, alcohol consumption, atrial fibrillation (AF), and myocardial infarction (MI). Main Outcome Measures: Adjusted hazard ratio (aHR) of RVOD, incidence rate of RVOD. Results: The incidence rate of RVOD per 100 000 was 495.3 in the AS group and 366.2 in the control group (P < 0.001). During a mean follow-up period of 8 years, the aHR of RVOD was 1.48 (95% confidence interval [CI]: 1.19–1.83) in the AS group compared with the control group. Even after adjusting for AF and MI, the incidence of RVOD remained consistently and significantly higher in patients with AS (aHR 1.29, 95% CI: 1.03–1.63). In the subgroup analysis based on age, the risk of RVOD was significantly higher in patients with AS across all age groups. However, this significance weakened after adjusting for MI in patients ≥80 years (aHR 7.47, 95% CI: 0.97–57.55) and for AF in patients ≥65 years (aHR 1.36, 95% CI: 0.92–2.03). Conclusions: The results suggest a possible clinical association between AS and subsequent RVOD. Continuous screening for ≥5 years for RVOD would be recommended in patients with AS. Financial Disclosure(s): The author(s) have no proprietary or commercial interest in any materials discussed in this article.